Preparing Future Indonesia Science Teachers through Microlearning: Effects on Pedagogical Competence and Instructional Readiness - Reni Marlina; Hamdani; Chokchai Yuenyong (Jurnal Pendidikan Sains Indonesia, 2026)
Preparing prospective science teachers with strong pedagogical competencies and instructional readiness remains an important challenge in teacher education. This study aims to evaluate the effectiveness of microlearning-based learning in improving the pedagogical competencies and instructional readiness of prospective science teachers. The study used a pretest–posttest quasi-experimental design with a control group. Participants consisted of 204 prospective science teacher. The experimental group received microlearning-based learning. The control group followed conventional learning methods. Data were collected using validated test instruments to measure pedagogical competence and instructional readiness, both of which had high reliability (Cronbach's alpha > 0.80). Data analysis was performed using independent and paired t-tests, analysis of variance, and effect size. The results showed that the experimental group had higher posttest scores for pedagogical competence (M = 4.31; SD = 0.41) than the control group (M = 3.62; SD = 0.47) with a large effect size (d = 0.86). Similarly, the instructional readiness scores of the microlearning group (M = 4.28; SD = 0.39) were significantly higher than those of the control group (M = 3.58; SD = 0.44) with a large effect size (d = 0.83; p < 0.001). These findings provide empirical evidence that microlearning-based learning is effective in improving the pedagogical competence and instructional readiness of prospective science teachers. This study confirms the potential of microlearning as a pedagogical approach that supports the strengthening of professional preparation in science teacher education and provides direction for the design of future teacher education.